Modulation of vulvovaginal atrophy (VVA) by Gelam honey in bilateral oophorectomized rats - Ismail, Nur Hilwani; Ibrahim, Siti Fatimah; Mokhtar, Mohd Helmy; Yahaya, Azyani; Zulkefli, Aini Farzana; Ankasha, Sheril June; Osman, Khairul (Frontiers in Endocrinology, 2023)
Vulvovaginal atrophy (VVA) is a common condition in post-menopausal women. Symptoms of VVA include dyspareunia, vaginal dryness, vaginal and/or vulvar itching, burning and soreness, dysuria and vaginal bleeding accompanying sexual activity. These symptoms are physiological responses to hypoestrogenicity, inducing atrophy of the vagina epithelia and sudden reduction in mucous production. Prevailing therapy for VVA is hormone replacement therapy (HRT), notably estrogen, progesterone or a combination of the two. However, using HRT is associated with an increased incidence of breast and endometrial cancer, venous thromboembolism in the lungs and legs, stroke and cardiovascular complications. This study evaluated Malaysian Gelam honey (GH) as a nutraceutical alternative to estrogen HRT (ERT) in alleviating VVA. A total of 24 female 8-week-old Sprague Dawley rats underwent bilateral oophorectomy. A minimum of 14 days elapsed from the time of surgery and administration of the first dose of Gelamhoney to allow the female hormones to subside to a stable baseline and complete recovery from surgery. Vaginal tissues were harvested following a 2-week administration of Gelamhoney, the harvested vagina tissue underwent immunohistochemistry (IHC) analysis for protein localization and qPCR for mRNA expression analysis. Results indicated that Gelamhoney administration had increased the localization of Aqp1, Aqp5, CFTR and Muc1 proteins in vaginal tissue compared to the menopause group. The effect of Gelam honey on the protein expressions is summarized as Aqp1>CFTR>Aqp5>Muc1. Gene expression analysis reveals Gelamhoney had no effect on Aqp1 and CFTR genes. Gelamhoney had up-regulated Aqp5 gene expression. However, its expression was lower than in the ERT+Ovx group. Additionally, Gelamhoney up-regulated Muc1 in the vagina, with an expression level higher than those observed either in the ERT+Ovx or SC groups. Gelamhoney exhibits a weak estrogenic effect on the genes and proteins responsible for regulating water in the vaginal tissue (Aqp1, Aqp5 and CFTR). In contrast, Gelamhoney exhibits a strong estrogenic ability in influencing gene and protein expression for the sialic acid Muc1. Muc1 is associated with mucous production at the vaginal epithelial layer. In conclusion, the protein and gene expression changes in the vagina by Gelamhoney had reduced the occurrence of vaginal atrophy in surgically-induced menopause models.